Beauty shop for rent-- : fully equipped, inquire within - Bowers, Laura, 1969- (Harcourt, 2007)
Raised by a great-grandmother and a bunch of beauty shop buddies, fourteen-year-old Abbey resolves to overcome her unhappy childhood and disillusionment with the mother who deserted her.